Characteristics of fractures stimulated by supercritical carbon dioxide fracturing in shale based on acoustic emission monitoring. (April 2022) - Wu, Shan; Ge, Hongkui; Li, Tiantai; Wang, Xiaoqiong; Li, Ning; Zou, Yushi; Gao, Ke
Abstract: In recent years, supercritical carbon dioxide (SC–CO2 ) has been attempted in hydraulic fracturing in shale reservoirs as a new type of fracturing tool to overcome the drawback of traditional water-based fluids. Because of the unique physical and chemical properties of SC-CO2, its fracturing mechanism is more complicated than traditional fluids and still unclear at present. In this paper, we hydraulically fracture a shale reservoir rock using SC-CO2 and monitor the fracturing process using acoustic emission (AE) data. The results show the fractures stimulated by SC-CO2 composite of both shear and tensile fractures. In the initiation stage, SC-CO2 activates the natural fractures around the wellbore and induces shear fractures. In the propagation stage, SC-CO2 permeates the fracture tips quickly, results in a dynamic propagation process, and generates plenty of tensile fractures. The phase change of CO2 could be observed during the fracture propagation process, which is accompanied by a rapid pressure change and local stress shock formations in the fractures. Additionally, the experiments also demonstrate that the existence of bedding structures in shale could constrain the propagation of fractures, thus leading to a smaller volume of fracture network and limiting the complexity of the generated fractures. This research may help understand the fracturing mechanism of SC-CO2 and shed light on the development of hydraulic fracturing technology in shale reservoirs.